Manifestaciones Orales En Pacientes De La Tercera edad con uso de prótesis dentales. Scoping Review. (2022)
n: During the process of dental care for elderly patients, different clinical findings and pathologies can be found at the level of their oral cavity, which are directly related to the use of dental prostheses, systemic diseases and harmful habits. In this population is where there is more deficiency in terms of oral hygiene in addition to lack of information on the care of the oral cavity.